Double Crosslinked Polymer Electrolyte by C–S–C Group and Metal–Organic Framework for Solid‐State Lithium Batteries. Issue 3 (14th March 2023) - Xu, Ruogu; Xu, Shengjun; Wang, Fei; Xiao, Ru; Tang, Pei; Zhang, Xiaoyin; Bai, Shuo; Sun, Zhenhua; Li, Feng
Abstract : Solid‐State Lithium Batteries In article number 2200206, Feng Li, Zhenhua Sun, and co‐workers report a double crosslinked poly(ethylene oxide)‐based polymer electrolyte by C‐S‐C groups and metal‐organic framework, which enables fast ion conduction and high stability. This cathode‐supported polymer electrolyte is developed for high‐energy solid‐state lithium batteries.